Reducing the incidence of oxyhaemoglobin desaturation during rapid sequence intubation in a paediatric emergency department. Issue 11 (16th July 2015) - Kerrey, Benjamin T; Mittiga, Matthew R; Rinderknecht, Andrea S; Varadarajan, Kartik R; Dyas, Jenna R; Geis, Gary Lee; Luria, Joseph W; Frey, Mary E; Jablonski, Tamara E; Iyer, Srikant B
Abstract : Objectives: Rapid sequence intubation (RSI) is the standard for definitive airway management in emergency medicine. In a video-based study of RSI in a paediatric emergency department (ED), we reported a high degree of process variation and frequent adverse effects, including oxyhaemoglobin desaturation (SpO2 <90%). This report describes a multidisciplinary initiative to improve the performance and safety of RSI in a paediatric ED. Methods: We conducted a local improvement initiative in a high-volume academic paediatric ED. We simultaneously tested: (1) an RSI checklist, (2) a pilot/copilot model for checklist execution, (3) the use of a video laryngoscope and (4) the restriction of laryngoscopy to specific providers. Data were collected primarily by video review during the testing period and the historical period (2009–2010, baseline). We generated statistical process control charts (G-charts) to measure change in the performance of six key processes, attempt failure and the occurrence of oxyhaemoglobin desaturation during RSI. We iteratively revised the four interventions through multiple plan-do-study-act cycles within the Model for Improvement. Results: There were 75 cases of RSI during the testing period (July 2012–September 2013). Special cause variation occurred on the G-charts for three of six key processes, attempt failure and desaturation, indicating significant improvement. The frequency of desaturation was 50% lower in the testing period than the historical (16% vs 33%). When all six key processes were performed, only 6% of patients experienced desaturation. Conclusions: Following the simultaneous introduction of four interventions in a paediatric ED, RSI was performed more reliably, successfully and safely.